Bedside Procedures in the ICU - Falter, Florian; SpringerLink (Online service) (London : Springer London, 2012)
At often critical times, ICU staff require immediate access to information regarding the management of patients in terms of procedures, drugs or any other aspect of treatment. Written by experts in the field of ICU, Bedside Procedures in the ICU facilitates rapid acquiring of clinical knowledge in a concise and didactic format. Focusing on the most commonly performed procedures in the Intensive Care Unit, this book examines 20 procedures all the way from indication to the management of possible complications. This easy to follow guide provides practical advice and essential background for every member of the multi-disciplinary team caring for critically ill patients, from the senior practitioner who has not performed a procedure for some time, to the junior doctor in need of step by step guidance.
Sedation and analgesia -- Airway Management and Intubation -- Bronchoscopy -- Percutaneous Dilatational Tracheostomy -- Arterial and Venous Catheter Insertion -- Advanced Non-Invasive Hemodynamic Monitoring -- Temporary cardiac pacing -- DC Cardioversion -- Pericardiocentesis -- Intercostal chest drain insertion -- Percutaneous Endoscopic Gastrostomy Tube Placement -- Gastroesophageal Balloon Tube Tamponade -- Acute Compartment Syndrome -- Abdominal Compartment Syndrome -- Ultrasound Guided Procedures -- Renal Replacement Therapy -- Lumbar Puncture -- External Ventricular Drain Insertion -- Intracranial Pressure Measurement.
Keywords: Medicine; Emergency medicine; Critical care medicine; Medicine & Public Health; Intensive / Critical Care Medicine; Emergency Medicine